2020
DOI: 10.3390/molecules25112647
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Percent Volume Buried in the Characterization of Copper(I) Complexes for Lighting Purposes

Abstract: The usefulness of percent volume buried (%Vbur) as a readily quantifiable property is investigated with regard to [Cu(NN)(PP)]+ complexes of interest for lighting purposes. Photoluminescence quantum yields (PLQYs) and single crystal X-ray structures of 100 reported compounds were assembled, %Vbur of the ligand systems were calculated and analyzed for correlations. We found that increased shielding of the central Cu(I) cation relying on shared contributions of both (NN) and (PP) ligand systems led to increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…In 2020 Alkan-Zambada et al have suggested a theory of the interdependence of buried volume (%V bur ) and photoluminescence QYs. On the example of 100 heteroleptic copper(I) diimine complexes, they have demonstrated that a high value of V bur is a necessary but insufficient condition for high photoluminescence QY [42]. Quite recently, the effect of the bite angle of the diphosphine ligand on the photoluminescence of the [Cu(NˆN)(PˆP)] + (NˆN = neocuproine) has been studied by Zysman-Colman et al [43].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020 Alkan-Zambada et al have suggested a theory of the interdependence of buried volume (%V bur ) and photoluminescence QYs. On the example of 100 heteroleptic copper(I) diimine complexes, they have demonstrated that a high value of V bur is a necessary but insufficient condition for high photoluminescence QY [42]. Quite recently, the effect of the bite angle of the diphosphine ligand on the photoluminescence of the [Cu(NˆN)(PˆP)] + (NˆN = neocuproine) has been studied by Zysman-Colman et al [43].…”
Section: Synthesismentioning
confidence: 99%
“…Based on the results obtained, we propose that the photophysical properties, especially photoluminescence QYs, of copper(I) complexes with Pyridine-pyrazoles and phosphines are affected by the steric effects of the ligands and the overall structural rigidity of complex, rather than by the donor ability of ligands. To our surprise, the role of the phosphine ligand has not been studied for the pyridine-pyrazole copper(I) complexes, even though the importance of the steric bulk has been demonstrated for bipyridine-containing analogs [42,43]. To confirm our hypothesis, we analyzed free volume around copper atoms in complexes 1-3 and in analogs [ Ph Pz Me PyCu(DPEPhos)]BF 4 that contain a Me substituent at the Py fragment and demonstrate comparable QY (71%) [40].…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…1 H-, 13 C{ 1 H}-and 31 P{ 1 H}-NMR spectra were recorded using a Bruker Avance III-500 NMR spectrometer (Bruker BioSpin AG, Fällanden, Switzerland) at 298 K. 1 H and 13 C NMR chemical shifts were referenced to residual solvent peaks with respect to δ (TMS) = 0 ppm and 31 P NMR chemical shifts with respect to δ (85% aqueous H 3 PO 4 ) = 0 ppm. Shimadzu LCMS-2020 (Shimadzu Schweiz GmbH, 4153 Reinach, Switzerland) and Bruker esquire 3000plus instruments (Bruker BioSpin AG) were used to record electrospray ionization (ESI) mass spectra with samples introduced.…”
Section: Generalmentioning
confidence: 99%
“…Typically, the P^P ligand is a wide bite-angle bisphosphane such as bis(2-(diphenylphosphanyl)phenyl)ether (POP) or (9,9-dimethyl-9 H -xanthene-4,5-diyl)bis(diphenylphosphane) (xantphos) ( Scheme 1 ) and these commercially available ligands remain the most popular choices. While structure–property relationships may be developed [ 12 , 13 , 14 ], enhanced PLQY is most often the result of trial-and-error structural variation of the N^N ligand. Synthetically, it is easier to vary the functionalities in the latter than in the P^P domain.…”
Section: Introductionmentioning
confidence: 99%
“…. π stacking, in the solid state strongly suppress the luminescence as seen in copper iodide complexes with 2,2 -bipyridyl or 1,10-phenanthroline ligands [18][19][20][21][22][23]. Therefore, the control of the intermolecular interaction in copper(I) iodide complex is also crucial for efficient luminescent materials.…”
Section: Introductionmentioning
confidence: 99%